"Corporatism With Adjectives"? Conceptualizing Civil Society Incorporation and Indigenous Participation in Latin America. (30th May 2013) - Chartock, Sarah
ABSTRACT Ethnodevelopment is a relatively new type of participatory policy that targets the poverty of marginalized ethnic groups with a focus on identity and self‐management. While observers have recognized the empirical significance of this new paradigm, little has been done to conceptualize ethnodevelopment. This article argues that national‐level ethnodevelopment implementation is a form of corporatism. Examining ethnodevelopment institutions in Ecuador, it shows that the state has structured, subsidized, and partially controlled the indigenous sector through ethnodevelopment policies and agencies. However, certain components of classical corporatism, such as monopolies of representation, do not characterize this paradigm. This article therefore classifies ethnodevelopment as a diminished subtype of corporatism. It challenges corporatism's long association with a particular historical period in the region and finds that Latin American states and social groups have called on historical institutional repertoires in responding to the newly salient ethnic cleavage in the region.